Respuestas
Respuesta dada por:
3
Primero calcularemos ![P(1) P(1)](https://tex.z-dn.net/?f=P%281%29)
![P(1)=3*1-4=3-4=-1 P(1)=3*1-4=3-4=-1](https://tex.z-dn.net/?f=P%281%29%3D3%2A1-4%3D3-4%3D-1)
Ahora calculamos![P(P(1)) P(P(1))](https://tex.z-dn.net/?f=P%28P%281%29%29)
![P(P(1))=P(-1)=3*-1-4=-3-4=-7 P(P(1))=P(-1)=3*-1-4=-3-4=-7](https://tex.z-dn.net/?f=P%28P%281%29%29%3DP%28-1%29%3D3%2A-1-4%3D-3-4%3D-7)
Luego,![F(3)=5*3-m=15-m F(3)=5*3-m=15-m](https://tex.z-dn.net/?f=F%283%29%3D5%2A3-m%3D15-m)
En efecto,
![P(P(1))=F(3)-14 \\ -7=15-m-14 \\ m=15-14+7 \\ m=8 P(P(1))=F(3)-14 \\ -7=15-m-14 \\ m=15-14+7 \\ m=8](https://tex.z-dn.net/?f=P%28P%281%29%29%3DF%283%29-14+%5C%5C+-7%3D15-m-14+%5C%5C+m%3D15-14%2B7+%5C%5C+m%3D8)
Saludos c:
Ahora calculamos
Luego,
En efecto,
Saludos c:
Anónimo:
GRACIAS
Preguntas similares
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años